2018
DOI: 10.1002/ptr.6095
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin is a substrate of OATP2B1 and OATP1B3

Abstract: The use and significance of baicalin, the main bioactive component found in Radix Scutellaria, have been on the rise due to its interesting pharmacological properties. Baicalin, a low passive permeability compound, is directly absorbed from the upper intestine and its hepatic elimination is dominant. However, interaction but no transport studies have implicated organic anion‐transporting polypeptides in its cellular uptake. By using mammalian cells stably expressing the uptake transporters of interest, we are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…A previous study has identified baicalin as a substrate for both OATP1B3 and OATP2B1 [36]. In our current study, the accumulation of baicalin in HEK-OAT1, HEK-OAT3, and HEK-OATP1B3 cells was about 4.0-, 3.9-, and 2.8-fold higher than that in HEK-EV cells, respectively (▶ Fig.…”
Section: Resultssupporting
confidence: 61%
“…A previous study has identified baicalin as a substrate for both OATP1B3 and OATP2B1 [36]. In our current study, the accumulation of baicalin in HEK-OAT1, HEK-OAT3, and HEK-OATP1B3 cells was about 4.0-, 3.9-, and 2.8-fold higher than that in HEK-EV cells, respectively (▶ Fig.…”
Section: Resultssupporting
confidence: 61%
“…After oral administration, BG, due to low lipophilicity, may either be directly absorbed by the action of uptake transporters, or undergo hydrolysis by intestinal glucuronidase or intestinal microflora to release its aglycone B (Akao et al., 2010; Kang et al., 2014; Noh et al., 2016; Kalapos-Kovács et al., 2018). B is probably better absorbed and then efficiently conjugated to BG in the gut wall and the liver and thus restored to its original form BG (baicalein 7-O-glucuronide) as well as to baicalein 6-O-glucuronide (Liu et al., 2009; Zhang et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Along with the growth in the clinical applicability of BG, there is increasing concern over the drug interactions with BG during coadministration with other agents ( Li-Weber, 2009 ; Boniface and Elizabeth, 2019 ). Notably, for treatment of patients with complex disease states, BG exhibited synergistic interactions with many combination drugs by regulating drug-metabolizing enzymes and/or drug transporters to decrease/enhance their efficacy and reduce/increase toxicity in the complex therapeutic regimens ( Kalapos-Kovacs et al, 2015 ; Kalapos-Kovacs et al, 2018 ; Zhou et al, 2021 ). We elucidated that BG varies the pharmacokinetics of phenacetin, theophylline, midazolam, dextromethorphan, nifedipine, and chlorzoxazone in rats by regulating the metabolism of CYP1A2, CYP2E1, CYP3A, and CYP2D in previous studies ( Gao et al, 2013 ; Tian et al, 2013a ; Tian et al, 2013b ; Cheng et al, 2014 ; Gao et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%